The Influence of Work Life Quality and Organizational Culture on Employee Engagement in PT. Wahyu Septyan Bengkulu - Attilah Nopriani; Suwarni Suwarni; Mimi Kurnia Nengsih (Penerbit Jurnal Indonesia, 2021)
The purpose of this study is (1) to find out the influence of work life quality on employee engagement in PT. Wahyu Septyan Bengkulu. (2) to find out the influence of organizational culture on employee engagement in PT. Wahyu Septyan Bengkulu. (3) to find out the influence of work life quality and organizational culture on employee engagement in PT. Wahyu Septyan Bengkulu. Quality of work life is a commitment to work and organization, pride in work and in the organization, a willingness to support the benefits of work, organization, and satisfaction, both emotional and intellectual. Organizational culture is the socialization process of organizational members to develop perceptions, values, and beliefs about the organization. Employee engagement is an employee's appreciation of purpose and concentration of energy, which appears in the form of initiative, adaptability, effort, and persistence toward organizational goals.This type of research is a quantitative that emphasizing its analysis on numerical data (numbers) which are processed by statistical methods. The sample used in this study using nonprobability sampling technique with saturated sampling. Researchers used this sampling technique because the population was 60 people. Data collection techniques using observation, questionnaires, and documentation. The data analysis technique of this research is multiple linear regression, t test and f test.The results of this study, (1) the work life quality has a significant influence on employee engagement with a sig value of 0.003. This means that when the work life quality in the company is getting better, it will increase employee engagement. (2)Organizational culture has a significant influence on employee engagement with a sig value of 0.001. This means that when the organizational culture in the company is getting better, it will be able to increase employee engagement. (3) the calculated of F count is 4.037. Because the value of F count 4.037> F table 3.16, as the basis for decision making in the F test it can be concluded that the hypothesis is accepted or in other words the work life quality (X1) and organizational culture (X2) simultaneously affect employee engagement (Y).